Analisis Yang Mempengaruhi Pertumbuhan Ekonomi Di Kabupaten Nias Utara Tahun 2012-2021 - wita mawati lase (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2023)
This study aims to determine the effect of the human development index, to find out how government spending influences, to find out how inflation influences, to find out how inflation, government spending and HDI influence economic growth in North Nias Regency. This research was conducted in North Nias District. Data analysis was carried out descriptively and multiple regression analysis. The results of the study show that the Human Development Index partially has a positive but not significant effect on economic growth. Government expenditure partially has a positive but significant effect on economic growth. Inflation partially has a positive but not significant effect on economic growth. Human Development Index, Government Expenditure and Inflation simultaneously (simultaneously). Keywords: Multiple Linear Analysis, Classical Assumption Test, Hypothesis Test